Methanolic Extract of Morinda citrifolia L. (Noni) Unripe Fruit Attenuates Ethanol-Induced Conditioned Place Preferences in Mice - Khan, Yasmin; Pandy, Vijayapandi (Frontiers in Pharmacology, 2016)
Phytotherapy is an emerging field successfully utilized to treat various chronic diseases including alcohol dependence. In the present study, we examined the effect of the standardized methanolic extract of Morinda citrifolia Linn. unripe fruit (MMC), on compulsive ethanol-seeking behaviour using the mouse conditioned place preference (CPP) test. CPP was established by injections of ethanol (2g/kg, i.p.) in a 12-day conditioning schedule in mice. The effect of MMC and the reference drug, acamprosate (ACAM), on the reinforcing properties of ethanol in mice was studied by the oral administration of MMC (1, 3 and 5g/kg) and ACAM (300 mg/kg) 60 min prior to the final CPP test postconditioning. Furthermore, CPPs weakened with repeated testing in the absence of ethanol over the next 12 days (extinction), during which the treatment groups received MMC (1, 3 and 5g/kg, p.o.) or ACAM (300 mg/kg, p.o.). Finally, a priming injection of a low dose of ethanol (0.4g/kg, i.p.) in the home cage (Reinstatement) was sufficient to reinstate CPPs, an effect that was challenged by the administration of MMC or ACAM. MMC (3 and 5g/kg, p.o) and ACAM (300 mg/kg, p.o.) significantly reversed the establishment of ethanol-induced CPPs and effectively facilitated the extinction of ethanol CPP. In light of these findings, it has been suggested that M. citrifolia unripe fruit could be utilized for novel drug development to combat alcohol dependence.